Pharyngeal transit time in different consistency of food using Fiberoptic Evaluation of Swallowing - Susyana Tamin; Mochamad Iqbal; Elvie Zulka Kautzia Rachmawati; Rahmanofa Yunizaf; Ratna Dwi Restuti; Aria Kekalih (PERHATI-KL, 2022)
ABSTRACTBackground: In Indonesia, no research has been carried out or reported on pharyngeal transit time and a view of the swallowing process in a sample without complaints of dysphagia using the Flexible Endoscopic Evaluation of Swallowing (FEES) method and using five food consistencies. Purpose: To obtain the value of pharyngeal transit time and a view of the swallowing process in subjects without dysphagia problems. Method: Twenty-eight subjects without dysphagia (based on Ohkuma’s Dysphagia Screening) underwent FEES to determine pharyngeal transit time and dysphagia profile based on leakage, standing secretion, residue, penetration, and aspiration. Result: The median value of pharyngeal transit time on puree consistency was 0.799(0.499-5.666), gastric rice 0.966(0.433-5.733), oatmeal 0.849(0.533- 4.399), thick liquid 0.982(0.399-4.633), thin liquid 0.566(0.366-1.366). The pharyngeal delay time on the puree consistency was 0.566(0.199-5.333), gastric rice 0.799(0.233-2.799), oatmeal 0.899(0.099-3.633), thick liquid 0.833(0.033-3.733), and thin liquid mean was 0.294 (± 0.232). The pharyngeal response time on the puree consistency was 0.566(0.167-1.300), gastric rice 0.583(0.300-2.934), oatmeal 0.583(0.367- 1.233), thick liquid 0.549(0.333-1.533), thin liquid 0.549(0.366-1.399). There was no standing secretion, pre-swallowing leakage, penetration, and aspiration found in FEES. A grade 1 residue was found in 3(10.7%) subjects of puree, in 2(7.2%) subjects of gastric rice, in 3(10.7%) subjects of oatmeal, and in 9(32.2%) subjects of thick liquid. Conclusion: There was no prolonged pharyngeal transit time, pre-swallowing leakage, standing secretion, penetration, and aspiration in all subjects without dysphagia complaints at all food consistencies. There was minimal residue within normal limits in some subjects. ABSTRAKLatar belakang: Di Indonesia, belum pernah dilaporkan penelitian mengenai waktu transit faring dan gambaran proses menelan pada sampel tanpa keluhan disfagia dengan menggunakan metode Flexible Endoscopic Evaluation of Swallowing (FEES) dan menggunakan lima konsistensi makanan. Tujuan: Penelitian ini bertujuan untuk memperoleh nilai waktu transit faring dan gambaran proses menelan pada subjek tanpa masalah disfagia. Metode: Dua puluh delapan subjek tanpa disfagia (berdasarkan Skrining Disfagia Ohkuma) menjalani FEES untuk menentukan waktu transit faring dan profil disfagia berdasarkan leakage, standing secretion, residue, penetration, dan aspiration. Hasil: Nilai median waktu transit faring pada konsistensi puree adalah 0,799(0,499-5,633), gastric rice 0,966(0,433-5,733), oatmeal 0,849(0,533-4,399), thick liquid 0.982(0.399-4.633), thin liquid 0.566(0.366- 1.366). Waktu tunda faring pada konsistensi puree adalah 0,566 (0,199-5.333), gastric rice 0,799 (0,233-2,799), oatmeal 0,899 (0,099-3,633), thick liquid 0,833 (0,033-3,733), dan rerata thin liquid 0,294 (± 0,232). Waktu respon faring terhadap konsistensi puree adalah 0,566 (0,167-1,300), gastric rice 0,583 (0,300-2,934), oatmeal 0,583 (0,367-1,233), thick liquid 0,549 (0,333-1,533), thin liquid 0,549 (0,366-1,399). Tidak didapati adanya leakage, standing secretion, penetration, dan aspiration pada pemeriksaan FEES. Residu grade 1 ditemukan pada 3 (10,7%) subjek puree, pada 2 (7,2%) subjek gastric rice, pada 3 (10,7%) subjek oatmeal, dan pada 9 (32,2%) subjek thick liquid. Kesimpulan: Tidak terdapat perpanjangan waktu transit faring, leakage, standing secretion, penetration, dan aspiration pada semua subjek tanpa keluhan disfagia dengan semua konsistensi makanan. Terdapat residu minimal dalam batas normal pada beberapa subjek.